2019
DOI: 10.26502/fccm.92920069
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography and 6-Minute Walk Test for Assessing Disease Progression in Systemic Lupus Erythematosus

Abstract: Introduction: Systemic lupus erythematosus is an autoimmune disease characterized by the production of antinuclear and cytoplasmic antibodies that can affect many organs. Cardiovascular diseases occurring in patients with SLE include myocardial infarction, coronary heart disease, stroke, transient cerebral ischemia, or thromboembolic disorders.Early identification of heart dysfunction in SLE is important in determining the course of the disease. Aim of the study:The aim of this study was to show the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the research, we have found that heart structure differs in SLE group, the left ventricular end-diastolic diameter was significantly higher than in the control group (45.60 ± 6.72 vs. 40.75 ± 6.83 mm, p =0.0247), and the LVEF on average was lower in that group (50.82 ± 7.01% vs. 57.68 ± 4.56%, p =0.0001) [ 25 ]. The SLE also had an impact on everyday lives, as study showed that during the 6-minute walk test, SLE patients covered much less distance than healthy adults (547.86 ± 87.59 vs. 595.37 ± 78.56 m, p =0.0472) and that activity of the disease was an important factor, as patients in regression achieved better results than patients with active SLE, according to the SLEDAI-2K (505.57 ± 75.55 vs. 582.35 ± 71.84).…”
Section: Discussionmentioning
confidence: 99%
“…In the research, we have found that heart structure differs in SLE group, the left ventricular end-diastolic diameter was significantly higher than in the control group (45.60 ± 6.72 vs. 40.75 ± 6.83 mm, p =0.0247), and the LVEF on average was lower in that group (50.82 ± 7.01% vs. 57.68 ± 4.56%, p =0.0001) [ 25 ]. The SLE also had an impact on everyday lives, as study showed that during the 6-minute walk test, SLE patients covered much less distance than healthy adults (547.86 ± 87.59 vs. 595.37 ± 78.56 m, p =0.0472) and that activity of the disease was an important factor, as patients in regression achieved better results than patients with active SLE, according to the SLEDAI-2K (505.57 ± 75.55 vs. 582.35 ± 71.84).…”
Section: Discussionmentioning
confidence: 99%